The Influence Of Islamic Branding, Muslim Fashion Trends And Brand Awareness On Purchasing Decisions Of Mangga Brand Sarongs (A Study On The Muslim Community In Salatiga City) - Praga Istira Setyo Pambudi; Edi Cahyono (Journal of Islamic Economics Management and Business (JIEMB), 2026)
Intense business competition and rapid technological advancements require companies to be able to produce high-quality products. It is crucial for companies to understand consumer behavior by incorporating Islamic branding trends, Muslim fashion trends, and brand awareness to meet consumer purchasing decisions. The purpose of this study was to determine the influence of Islamic Branding, (X1), Muslim Fashion Trends (X2), and brand awareness (X3) on purchasing decisions for Sarung Cap Mangga (Y). This study used a quantitative method with data collection using a questionnaire distributed to 160 users of Sarung Cap Mangga in Salatiga. The data obtained were then processed using Smartpls 4 with analysis Iner model and Outer model Data analysis in this study included instrument data testing, classical assumption testing, and statistical tests. Based on the t-test results, it was shown that Islamic Branding had a positive but insignificant effect on purchasing decisions for Sarung Cap Mangga. Muslim Fashion Trends in the community had a positive and significant effect on purchasing decisions for Sarung Cap Mangga among Muslims in Salatiga City. Brand awareness had a positive and significant effect on purchasing decisions for Sarung Cap Mangga among Muslims in Salatiga City. This study can provide insights for businesses to develop more effective marketing strategies. These findings underscore the importance of additional factors such as price, product quality, brand image, halal lifestyle, consumer satisfaction, and trust in the brand, along with the presence of moderating or intervening variables